Flexible work system inclusion requirements - Hind lebsir (Dirassat Journal Economic Issue, 2016)
Fixed work is based on adherence of staff with constant daily and weekly working hours. Although it ensures the presence in one place and specific times, this system is not without disadvantages and weaknesses. So it was resorting to a system that accommodates economic, technological and social developments; it is a flexible working system, which offers the possibility of modifying the work schedule in order to double interest between the employee and the organization.However, the practices of the system of flexible working require the availability of a group of external and internal requirements such as the availability supportive laws for its application and to support both the managers and staff of the system.